Análise dos efeitos da fadiga muscular no sinal eletromiográfico de superfície em contrações dinâmicas do bíceps braquial - Linhares, Nicolai Diniz (2015)
The muscle fatigue can be caused by multiple factors, and the most common one is bodywork. As a result, the muscle stress signal becomes part of atlets life. However, this phenom may show injuries incident, neuromuscular diseases, and it is related to the general human being health, as well as with its nutrition. To determine the fatigue level from a muscle or from a person is not that simple, because multiple subjective factors are envolved, including psychological and hormonal matters, thus maybe is not possible to determine an universal method for quantification of muscle fatigue. The electromyographic signal (EMG) is well known and studied for reflecting the musculature condition from which it was generated. The electromyography is an important tool for the health muscle assessment, and counts on various studies and advances in its formation and interpretation understanding.Thus, it is expected that the muscle fatigue that affects the natural muscle behavior, affects also the EMG signal. This work aims to understand how the fatigue action appears in the signal, through the study of different EMG signal characteristics. From literature, several studies analyzed isometric contractions, thus it was decided to make a dynamic contractions evaluation, which are more natural in the daily life. For the sake of simplicity, the biceps braquii was chosen. This muscle was estimulated by a scott biceps curl exercise, an exercise known to well isolate the working muscle, so that the weight lifting is almost all done by the biceps action. Pilot trial was done, collecting EMG signals from both biceps braquii, and also measuring the force applied to the bar. For the EMG signal analysis, three software packages were developed. One of them was a programm for the electromyographer control, and for the signals record- ing in text files without header. For this development were used C Sharp and .NET. One library for signals processing was developed using Matlab, including fil- ter functions, muscle activity detection and features extraction, such as amplitude, frequency, entropy, and stationarity. Finally, was developed a programm for feature analysis that uses the previous mentioned library, and that also applies the Kohonen algorithm of self-organizing maps.This programm was also developed using Matlab. All created programms are open source, and they are available for download on GitHub platform. A temporal analysis of the features was performed in order to cluster the results of the features extracted from the signals of 21 volunteers. This analysis showed that signal s amplitude increases as the fatigue occurs while there is a spectral shift for the left. This shift indicates that the main frequencies have decreased. The trends observed for amplitude and frequency are the same reported in the literature. The results also show decreasing in the entropy as effect of the fatigue progres- sion. Two stationarity features indicate decreasing in the stationarity, these were influenced by the amplitude raise, though. A third stationarity feature, which is not dependent on amplitude, show that there is not significant modification on the stationarity. The data clustering attempt using the Kohonen algorithm was frustrated, gener- ating inconclusive results. It can be concluded that the features related to amplitude, frequency and entropy are somehow related to the muscular fatigue. So that it is possible, during future work, the development of a fatigue classifier based on these features.